Brief Report: Under-Representation of African Americans in Autism Genetic Research: A Rationale for Inclusion of Subjects Representing Diverse Family Structures - Hilton, Claudia L.; Fitzgerald, Robert T.; Jackson, Kelley M.; Maxim, Rolanda A.; Bosworth, Christopher C.; Shattuck, Paul T.; Geschwind, Daniel H.; Constantino, John N. (Journal of autism and developmental disorders, 2010)
African American children with autism are seriously under-represented in existing genetic registries and biomedical research studies of autism. We estimated the number of African American children with autism in the St. Louis region using CDC surveillance data and present the outcomes of a concerted effort to enroll approximately one-third of that population into either of two large national genetic autism registries. The results revealed that even after traditional barriers to research participation were addressed and all contacted families expressed a willingness to participate, 67% of the reachable families were disqualified from participation because of family structure alone. Comprehensive efforts—including expansion of eligibility to families of diverse structure—are warranted to facilitate the inclusion of African American children in biomedical research.